Methods for computation of solutions to regular discrete-time linear systems - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
Two new methods for the computation of solutions to regular discrete-time linear systems are presented. The first of them is an extension of the Diasesquista method for regular discrete-time linear systems. The other is based on an expansion in a series of the inverse matrix [Ez - A]-1.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka